SEMANTICALLY AWARE CONTENT-BASED E-LEARNING RECOMMENDATIONS: ENHANCING PERSONALIZED LEARNING EXPERIENCES - Qhaliza, Bonny; Kharisma, Adib Jasni (Universitas Islam Sumatera Utara, 2024)
E-learning, or electronic learning, is a form of online education exclusively accessible via the internet. With internet connectivity, users can access e-learning materials from any location and at any time. Post-pandemic, e-learning has emerged as a favored mode of remote education, offering flexibility and accessibility to learners worldwide. Since the onset of Covid-19, e-learning has surged in popularity, becoming a preferred platform for educational endeavors. In qualitative research, questionnaires and interviews serve as primary data collection methods. Conducting interviews with individuals connected to the research topic is essential for gathering qualitative data effectively. The aim of this study is to identify the most widely used e-learning resources among students. The study's findings reveal a preference for video content among students utilizing e-learning platforms. Out of the 24 respondents surveyed, 14 (58.3%) reported choosing video-based learning as their preferred method, citing its effectiveness in facilitating comprehension. Utilizing video content in e-learning enhances students' understanding of the material, as indicated by the study's outcomes. To optimize the efficacy of e-learning video content, regular updates are crucial to sustain student engagement and ensure the content remains relevant and compelling.